ANALISIS BERBAGAI STRATEGI GURU DALAM PEMBENTUKAN KARAKTER SISWA - Saputra, Robi; Amriyah, Chairul; Sunarto, Sunarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the various strategies employed by teachers in shaping students' character at school. The research was motivated by the increasing challenges of character education in the modern era, including issues related to discipline, responsibility, honesty, and social behavior among students. This study employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving teachers, school principals, and students as research informants. The validity of the data was ensured through source triangulation and technique triangulation, while data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that teachers applied various strategies in character building, including exemplary behavior, habituation, advice and motivation, as well as discipline enforcement. Among these strategies, exemplary behavior emerged as the most dominant approach because students tend to imitate the attitudes and behaviors demonstrated by their teachers. The study also found that the success of character education is supported by positive school culture, collaboration among teachers, and parental involvement, while peer influence, excessive social media use, and limited parental supervision remain significant challenges. Therefore, character formation requires the integration of multiple strategies and cooperation among schools, families, and communities. Keywords: teacher strategies, character education, character building.